3D Macroscopic Architectures from Self‐Assembled MXene Hydrogels. (13th June 2019) - Shang, Tongxin; Lin, Zifeng; Qi, Changsheng; Liu, Xiaochen; Li, Pei; Tao, Ying; Wu, Zhitan; Li, Dewang; Simon, Patrice; Yang, Quan‐Hong
Abstract: Assembly of 2D MXene sheets into a 3D macroscopic architecture is highly desirable to overcome the severe restacking problem of 2D MXene sheets and develop MXene‐based functional materials. However, unlike graphene, 3D MXene macroassembly directly from the individual 2D sheets is hard to achieve for the intrinsic property of MXene. Here a new gelation method is reported to prepare a 3D structured hydrogel from 2D MXene sheets that is assisted by graphene oxide and a suitable reductant. As a supercapacitor electrode, the hydrogel delivers a superb capacitance up to 370 F g −1 at 5 A g −1, and more promisingly, demonstrates an exceptionally high rate performance with the capacitance of 165 F g −1 even at 1000 A g −1 . Moreover, using controllable drying processes, MXene hydrogels are transformed into different monoliths with structures ranging from a loosely organized porous aerogel to a dense solid. As a result, a 3D porous MXene aerogel shows excellent adsorption capacity to simultaneously remove various classes of organic liquids and heavy metal ions while the dense solid has excellent mechanical performance with a high Young's modulus and hardness. Abstract : A new MXene gelation method is demonstrated by assembling MXene flakes into a 3D hydrogel in the presence of graphene oxide and ethylene diamine. The resulting hydrogel shows an ultrahigh capacitance and an exceptionally high rate performance for supercapacitors and is ready to produce a MXene porous aerogel and dense solid with great promise in pollutant removal and compact energy storage.